2019
DOI: 10.1177/1528083719833976
|View full text |Cite
|
Sign up to set email alerts
|

Tensile behavior of virgin and recycled polyester nonwoven filter fabrics

Abstract: This study deals with two different categories of needle-punched nonwoven fabric samples developed from virgin and recycled polyester fibers. To understand the effect of tensile behavior (strength and extension) of these filters, fabric samples have been developed varying fabric weight, needling density and depth of needle penetration. This study also established the efficacy of use of recycled polyester for preparation of filter fabric. The study revealed that the tensile strength of fabric made using recycle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 4 publications
1
3
0
Order By: Relevance
“…The differences in the stress levels of the different PSF and backing free-TFC membranes at different orientations are minimal and can be neglected when compared to the differences in the case of polyester and polyester-supported samples; thus, it could be concluded that the polyester layer dominated the anisotropic behavior of the entire RO membrane, due to the fact that it has a nonwoven structure ( Figure 6 ). These findings match the results presented by Chauhan et al [ 25 ], Pramanick et al [ 26 ], and Ray et al [ 27 ]. They assessed the nature of anisotropy in terms of tensile properties for nonwoven fabrics.…”
Section: Resultssupporting
confidence: 93%
“…The differences in the stress levels of the different PSF and backing free-TFC membranes at different orientations are minimal and can be neglected when compared to the differences in the case of polyester and polyester-supported samples; thus, it could be concluded that the polyester layer dominated the anisotropic behavior of the entire RO membrane, due to the fact that it has a nonwoven structure ( Figure 6 ). These findings match the results presented by Chauhan et al [ 25 ], Pramanick et al [ 26 ], and Ray et al [ 27 ]. They assessed the nature of anisotropy in terms of tensile properties for nonwoven fabrics.…”
Section: Resultssupporting
confidence: 93%
“…very wide, such as sound absorber (Özkal and Cengiz Çallıoğlu 2020), apparel (Anderson 2005), medical textiles (Mothilal et al 2019), automotive textiles (Atakan et al 2018), filters (Chauhan et al 2019), sanitary masks (Opálková Šišková et al 2020), and packaging (Lin et al 2018).…”
Section: Recycled Pet Fibersmentioning
confidence: 99%
“…The fabrics such as cotton, polyester (PE), polyethylene terephthalate (PET) and polypropylene (PP) is closely related to people's lives. [12][13][14] For example, PE NWF is widely used in biomedical applications and endowing the fabrics with antibacterial property can avoid the direct and indirect spread of microorganisms in certain circumstances. Therefore, it's of great significance to develop antibacterial modified fabrics in both scientific and practical areas.…”
Section: Introductionmentioning
confidence: 99%